STUDY ON CONSTRUCTION OF BOAT LIFT NET 30 GT IN SIBOLGA FISHING PORT PONDOK BATU DISTRICT NORTH SUMATRA - Sagala, Ivanson; Syofyan, Irwandy; ', Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study was conducted on 09-23 May 2016 is located in Sibolga Fishing Port. The purpose of this study to collect information on the construction of boat lift net. The method used was survey and observation. Observed object is boat lift net used on vessels 30 GT. Data collection was performed by means of measurements on sample.The results of the research indicated that the construction of boat lift net used in PPN Sibolga consists of importants components of boat, frame lift net, house boat lift net, pole line, wire, webbing, rope, lamp and instrumentation. Differences were found on a boat lift net in PPN Sibolga is not having leeboard.Keywords: Construction of Fishing Gear, Boat lift net, Sibolga Fishing Port